Analysis of Medicinal Plant Potential in the Nglanggeran, Gunungkidul, Yogyakarta - Hikmah Supriyati; Widodo Widodo (Biology, Medicine, & Natural Product Chemistry, 2026)
Indonesia has abundant biodiversity with thousands of plant species traditionally used as medicine. The role of medicinal plants is increasingly recognised amid the trend of returning to nature and seeking more sustainable health solutions. Nglanggeran has a physical, chemical, and biotic environment that differs significantly from other ancient volcanoes in Indonesia. This situation is one of the reasons for Nglanggeran's unique flora. This study aimed to identify medicinal plants in Nglanggeran. The methods used in this study were surveys and exploration. The study results show that there are 21 families and 35 plant species with medicinal properties in Nglanggeran. The Euphorbiaceae family has the most medicinal plants. The most common habitus of medicinal plant species found in Nglanggeran is shrub. Leaves are the most widely used part of medicinal plants for treatment. Based on a literature review, most medicinal plants in Nglanggeran have undergone phytochemical testing. The compounds most commonly found in these plants are flavonoids and alkaloids.